Spatial variability of physical properties: relationship with relief, organic matter and productivity in Conilon coffee - Burak, Diego Lang; Santos, Danilo Andrade; Passos, Renato Ribeiro (Coffee Science - ISSN 1984-3909, 2017)
Soil attributes may be influenced by the relief generating homogeneous productivity zones. From this hypothesis, we identified soil attribute groups, its spatial variability and relationship with productivity and relief by Factor Analysis (FA) and geostatistics methods. The study was conducted in a Oxisol cultivated with Conilon coffee in the State of Espírito Santo. The AF group in Factor 1 (F1) attributes related to soil aggregation was not associated with relief and productivity. Its spatial variability is influenced by management as showed by the lower spatial continuity and dependence in 0 – 0.10 m depth and by pure nugget effect in 0.10 – 0.20 m depth. From the factor 2 (F2), obtained in two depths, can be grouped soil attributes related to water retention, mainly the clay, microporosity and moisture which together increase at a higher altitude and lower slope where occur higher productivity areas. The spatial variability of F2 indicates greater continuity and spatial dependence, suggesting influence of relief in the spatial variation structure.